A utilização dos brinquedos no processo de ensino aprendizagem da natação - Rocha, Kássia Ferreira da (2014)
The research approaches the motor development e its phases, as well as the element of playing and the toy during childhood, a summary of swimming and children swimming, relating between those areas. The purpose was to identify which are the strategies of interference used by the teacher during the teaching-learning swimming process. The research includes the participation of 7 teachers tha work with the teaching-learning swimming process for children between the ages of 0 to 3 years old, belonging to three swimming schools that were choosen intentionally. For the data collection, a structrured interview was applied featuring seven questions in order to pick up the sense of the interviwee regarding the teaching-learning children swimming process.The interview was transcripted and following that, discussed along with the adequate literature. Based on this discussion, it came to the conclusion that teachers do not use toys as a pedagogic tool in the teaching-learning swimming process for children between the ages of 0 to 3 years old.